(untitled) (Revista de Ciências Agroveterinárias, 2025)
Jambi Province is one of the areas that is developing Liberica coffee plants. The unique thing about Liberica coffee is that it grows well in peatlands with high acidity levels. However, poor post-harvest processes and lack of treatment can reduce the quality of Liberica coffee. Fermentation is a metabolic process that uses sugar both aerobically and anaerobically. Fermentation of coffee can increase the cupping test value and influence its antioxidant activity. This research aims to analyze the effect of artificial liberica Civet Coffee in vitro using a stainless bioreactor on the sensory profile and proximate analysis. The research began with bioreactor design, fermentation process, and analysis of Liberica Coffee’s fermentation results. The results showed that fermentation increased ash content, reduced fat content, and increased water content in vitro. Apart from that, the highest fermentation waste gas using a bioreactor is CO2, reaching 400 ppm. The sensory profile of Liberian coffee fermented in vitro using a bioreactor increases the sensory value from 80.41 to 81.75 but is still lower than fermentation without a bioreactor, 86.30. Our findings revealed that fermentation can improve the sensory profile of Liberica coffee and is promising to increase the value of the Liberica coffee commodity.